Experimental and environmental analysis of new sound-absorbing and insulating elements in recycled cardboard. (March 2016) - Secchi, Simone; Asdrubali, Francesco; Cellai, Gianfranco; Nannipieri, Elisa; Rotili, Antonella; Vannucchi, Irene
Abstract: Paper and cardboard, made with recovered fibers obtained by recycling, are an attractive, sustainable material. Recovered paper and cardboard are mainly used for packaging purposes, even if, in recent years, various researches focused on the possibility to develop new products and proposed alternative applications. This paper presents new designs of acoustic absorbers made of partially recycled cardboard, in order to reduce the environmental impact of the materials usually used for the acoustic correction on indoor environments. Some of these new designed absorbers are porous and make use of the visco-thermal absorption effects in the pore space. Other absorbers are based on the Helmholtz resonator principle. Computer modeling software was used to predict the performance of the absorbers; in particular, different options of cardboard-based panels and paperboard tubes were investigated to identify the solutions with the best acoustic performance. A real-size prototype of a sandwich panel was then experimentally characterized in laboratory. The absorption coefficient spectrum of the prototype was measured according to the procedure indicated in the ISO 354 standard. The results show that the measured acoustic absorption coefficient of the material made using cardboard was higher than the one of traditional gypsum absorbers, giving in particular an increase of the acoustic absorption at mid and high frequencies in the order of 40%. A Life Cycle Assessment analysis was also performed to evaluate the environmental advantages of these materials. The environmental impacts of the production of the cardboard-based panel were compared with the impacts of conventional acoustic materials. The analysis highlighted a potential reduction of both energy demand and greenhouse gas emissions during the production process of the cardboard-based acoustic materials. The estimated CED and GWP values result 10% and 34% respectively lower than the impacts of a conventional gypsum board. Highlights: Acoustic and environmental performance of new acoustic absorbers made of recycled cardboard were investigated. The most promising product is made of two panels of honeycomb cardboard filled with cellulose fibers. The acoustic absorption coefficient of the sandwich panel is higher than the ones of other traditional absorbers. The LCA shows that GWP and CED values are lower than the ones of a traditional acoustic materials.